Efeito de Aditivos no Valor Nutritivo de Silagens feitas com Subproduto da Extração do Palmito de Pupunha (Bactris gasipaes H.B.K.) - Neto, Antonio José Rodrigues; Bergamaschine, Antonio Fernando [UNESP]; Isepon, Olair José [UNESP]; Alves, João Batista [UNESP]; Hernandez, Fernando Braz Tangerino [UNESP]; Macedo, Marcelo Pereira [UNESP] (My University, 2001)
The objective of this experiment was to evaluated the effect of additives on the quality and nutritive value of silages made with pejibaye palm by-product, according to the following treatments: T1 - Control (without additive); T2 - Addition of 2.5% of sugar; T3 - Addition of 10.0% of citric pulp and T4 - Addition of 10.0% of ground corn, based on natural matter. The use of 10.0% of citric pulp (CP) or ground corn (GC) increased dry matter content of the by-product prior to ensilage and of the silage by 6,5 and 8,0 percentage units, respectively. The use of additives resulted in smaller values of ammoniacal nitrogen (N-NH3/TN) and pH. Dry matter intake was higher for silage made with CP or GC, mean value of 85.0 g/kgLW0.75 or 2.1% of LW, compared to the others (44.7 g/kgLW0.75 or 1.12% of LW). Also, apparent dry matter digestilibity coefficient was higher for silage containing 10% CP or GC (65.0%) in comparison to the others (52.07%). Cell wall digestibility did not show a defined trend as a function of the treatments. Silage made of by-product pejibaye with 10.0% of citrus pulp or ground corn showed a nutritional value similar to conventional forage silages.
Effect of Additives on Nutritive Value of Silages Based on Palm Cabbage Production By-products from Pupunha (Bactris gasipaes)
Keywords: Citric pulp; Digestibility; Intake